Promotional Media Needs in Capacity Building of Health Cadres in Rural Areas: A Qualitative Study in Lebak District - Nintinjri Husnida; Kadar Kuswandi; Tutik Iswanti; Melly Halimatussa’adiah (Poltekkes Kemenkes Surabaya, 2025)
Health cadres play an important role in community health promotion, especially in rural areas. However, the process of empowering and training cadres has not always been effective in achieving the expected goals. This study aims to explore the knowledge, barriers, and needs of cadres related to child growth and development, so that health workers can design appropriate learning media and methods. This study used a qualitative phenomenological approach and was conducted in the Mandala Rangkasbitung Health Centre Working Area, Lebak Regency, Banten Province, in June-October 2024. The results showed that the cadres' knowledge about children's growth and development was quite good. However, they experienced difficulties in explaining the material to the community due to limited media. Cadres expressed the need for simple, pictorial health promotion media with written explanations to support their work. Therefore, traditional media such as leaflets or posters with a flip-sheet format are urgently needed to improve the effectiveness of health promotion by cadres.